Pengaruh Literasi Keuangan terhadap Efektivitas Pengelolaan Keuangan Lab School Unismuh Makassar - Akbar Riyansyah; Ismail Badolahi; Idil Rahmat Susanto (Indonesian Journal of Research in Economy, 2026)
Effective financial management is essential for educational institutions that manage multiple funding sources and must maintain transparency and accountability. This study examines the effects of financial knowledge, financial attitude, and financial skill on financial management effectiveness at Lab School Unismuh Makassar. An explanatory quantitative design was used. Data were collected through a structured questionnaire from 40 purposively selected respondents directly involved in school financial planning, implementation, recording, reporting, and supervision. Data were analyzed using descriptive statistics, validity and reliability tests, and multiple linear regression. Financial knowledge (B = 0.668; β = 0.255; p < 0.001), financial attitude (B = 1.037; β = 0.389; p < 0.001), and financial skill (B = 1.090; β = 0.479; p < 0.001) had positive and significant effects. Simultaneously, the three predictors significantly explained financial management effectiveness (F = 175.811; p < 0.001; R² = 0.936). Financial skill was the most dominant predictor. The findings indicate that stronger school financial governance requires an integrated improvement of conceptual knowledge, responsible attitudes, and practical competencies in budgeting, transaction recording, reporting, and financial control.